2013
DOI: 10.1038/onc.2013.328
|View full text |Cite
|
Sign up to set email alerts
|

RKIP and HMGA2 regulate breast tumor survival and metastasis through lysyl oxidase and syndecan-2

Abstract: Elucidating targets of physiological tumor metastasis suppressors can highlight key signaling pathways leading to invasion and metastasis. To identify downstream targets of the metastasis suppressor Raf Kinase Inhibitory Protein (RKIP/PEBP1), we utilized an integrated approach based upon statistical analysis of tumor gene expression data combined with experimental validation. Previous studies from our laboratory identified the architectural transcription factor and oncogene, HMGA2, as a target of inhibition by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(69 citation statements)
references
References 55 publications
0
66
0
3
Order By: Relevance
“…These interactions frequently depend on the sulfation characteristics of the binding HSPG and mediate roles in adhesion that can affect cancer cell proliferation. For example, SDC2 promotes cell adhesion and associated proliferation, and decreasing SDC2 expression results in cell cycle arrest and decreased colon and breast cancer tumorigenesis [21, 22]. SDC2 is overexpressed in tumors of the breast, colon, prostate, and bladder, as well as gliomas and sarcomas [17].…”
Section: Hs In Cancer Cell Proliferationmentioning
confidence: 99%
“…These interactions frequently depend on the sulfation characteristics of the binding HSPG and mediate roles in adhesion that can affect cancer cell proliferation. For example, SDC2 promotes cell adhesion and associated proliferation, and decreasing SDC2 expression results in cell cycle arrest and decreased colon and breast cancer tumorigenesis [21, 22]. SDC2 is overexpressed in tumors of the breast, colon, prostate, and bladder, as well as gliomas and sarcomas [17].…”
Section: Hs In Cancer Cell Proliferationmentioning
confidence: 99%
“…RKIP also de-represses GSK3β inhibition which, in turn, inhibits β-catenin, Snail and Slug activation with expected modulation of EMT [92]. Recent data, also from the Rosner group, show that RKIP induces and HMGA2 inhibits miR-200b expression which, in turn, inhibits expression of lysyl oxidase (LOX) [93]. Also via down-regulation of HMGA2, RKIP inhibits syndecan-2 independently of miR-200 [93].…”
Section: Raf Kinase Inhibitor Protein (Rkip)mentioning
confidence: 98%
“…Recent data, also from the Rosner group, show that RKIP induces and HMGA2 inhibits miR-200b expression which, in turn, inhibits expression of lysyl oxidase (LOX) [93]. Also via down-regulation of HMGA2, RKIP inhibits syndecan-2 independently of miR-200 [93].…”
Section: Raf Kinase Inhibitor Protein (Rkip)mentioning
confidence: 99%
“…These analyses identified three additional downstream targets of RKIP and HMGA2: miR-200, lysine oxidase (LOX), and syn-decan 2 (SDC2). 42 miR-200 has been implicated in breast tumor cell initiation and the epithelial-mesenchymal transition that leads to cell invasion. 32 LOX is a known collagen and elastin cross-linker that helps invasion and metastasis.…”
Section: Rkip-regulated Signaling Modulesmentioning
confidence: 99%
“…This is confirmed by random survival forest (RSF) analysis of these genes, which showed that these genes cooperate in patient stratification, especially in low-RKIP tumors. Other gene signatures were also derived based on RKIP, HMGA2, LOX, and SDC2, 42 and the HMGA2, TET1, HOXAA7, and HOXA9 networks. 45 The general strategy for developing pathway gene signatures in this manner has been described previously.…”
Section: Potential Clinical Applications Of Rkip Signaling Pathwaysmentioning
confidence: 99%